EDUCATION OF SELF-CONFIDENCE IN OLDER TEENAGERS IN THE PROCESS OF JUDO CLASSES - Shmatko, Yaroslav (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article updates the issues of education of older teenagers’ self-confidence in the process of judo classes. It is emphasized that this type of sport has a significant resource potential for the development of moral and volitional qualities of an individual.The purpose of the article is to determine the influence of sports and recreational activities (judo classes) on education of older teenagers’ self-confidence.The main tasks are: to actualize education of older teenagers’ self-confidence in the process of judo classes; to define the main tasks of this type of judo classes; to determine the reasons why older teenagers participate in sports and recreational activities (in particular, in judo classes); to study moral and volitional qualities that older teenagers want to develop in themselves during judo classes; to highlight the factors that are the most essential for educating older teenagers’ self-confidence in the process of judo classes.To achieve the goal and solve the research tasks, theoretical, empirical and statistical methods of data compilation and processing were used (self-analysis, self-assessment, questionnaires, quantitative and qualitative data analysis, and expert evaluation). 118 specialists of physical education and sports, 162 male and female students from Kyiv, Odesa, Vinnytsia, Chernihiv, and Ternopil regions took part in the survey.The survey results on the reasons why older teenagers participate in sports and health activities and the qualities they want to develop in themselves in judo lessons are highlighted. It is determined that in the process of judo classes, it is important for older teenagers to educate moral and willpower qualities that help them feel confident in their own abilities, have experience of self-support, take on the role of a leader, achieve set results, as well as be resistant to external and internal influences.The factors that are the most important for educating older teenagers’ self-confidence in the process of judo classes are analyzed: the meaningful content of classes; orientation of forms and methods of work on the education of moral and volitional qualities; systematicity; competitive activity; regularity; duration and intensity of classes.